Annual alveolar bone loss in older adults taking oral bisphosphonate: a retrospective cohort study - Mohammad Helmi; Sara AlOsaimy; J. Max Goodson; Hatice Hasturk; Zuhair S. Natto (BMC, 2019)
Abstract Background Although several studies assessed the effect of bisphosphonate (BIS) administration on alveolar bone loss, this relationship has not been fully investigated using longitudinal analysis. The aim of the this article is to predict annual alveolar bone loss in a subpopulation of older adults patients who were taking oral bisphosphonate (BIS), adjusting for systemic diseases and associated risk factors. Methods This is a retrospective cohort study. We identified all subjects who reported receiving oral bisphosphonate from 2008 to 2015 (N = 30) using the electronic health records of each patient to identify suitable radiographs for analysis. For the longitudinal data analysis, 26 subjects were eligible for inclusion, having at least two exposures of the complete mouth set or repeated bitewing radiographs at least a one-year interval; they were then matched on age and sex to another 26 patients who did not report receiving bisphosphonate at any point of their life. Results Mild periodontitis was higher in the BIS group compared to the no BIS group; however, moderate periodontitis was higher in the no BIS group. For those who did not take oral BIS, change over time was not significant after the two-year period. However, the BIS group had experienced 0.088 mm more bone loss compared to the no BIS group (95% CI: 0.001, 0.176. P-value = 0.048), adjusting for all other variables included in the model. Conclusion The group that reported receiving oral bisphosphonates showed no improvement in maintaining alveolar bone level, and the use of oral BIS may not be effective in reducing annual alveolar bone loss; however, emerging evidence is promising for the use of bisphosphonate as an adjunctive local delivery medication for the management of periodontal diseases.